Analisis Seng Dan Besi dalam Air Minum Mineral Isi Ulang yang Berada di Kota Surakarta dengan Metode Spektrofotometri Serapan Atom - SEPTINA DYAH NUGRAENI; - SUPRIYADI; RESLELY HARJANTI (Jurnal Farmasi Indonesia, 2012)
The mineral water is water that obtained directly from it sources, then processed with special treatment and packed. Mineral water may contained metal contamination, such as zinc and iron, which comes from water distribution pipes, production equipment, or even from other source that contains zinc and iron. Zinc and iron in large amount can cause toxicity for the body. This research aimed to know presence and amount of zinc and iron in refill drinking mineral water by atomic absorption spectrophotometry method. Samples were acidified with concentrated HNO3, then were evaporated and analyzed by qualitative and quantitative method. The amount obtained by entering absorbance data obtained from standard mutual curve regression equation. The research results showed that all samples of refill mineral drinking water are containing zinc and iron. The zinc content of the sample A (0.0011 ± 0.0005) ppm, the sample B (0.0019 ± 0.0000) ppm, sample C (0.0100 ±0.0004) ppm. The iron content of sample A (0.0176 ± 0.0015) ppm, the sample B (0.0176 ± 0.0015) ppm, sample C (0.0187 ± 0.0022) ppm. The amount of zinc and iron in three drinking water samples met the requirements set by the Indonesian National Standard No. 01-0220 - 1987.